A conserved role for calpains during myoblast fusion. Issue 7 (14th July 2015) - Buffolo, Marcio; Batista Possidonio, Ana Claudia; Mermelstein, Claudia; Araujo, Helena
Summary Myoblast fusion is a key step during skeletal muscle differentiation as it enables the formation of contractile fibers. Calpains have been implicated in some aspects of myogenesis in mammals, but whether they exert a conserved function during myoblast fusion has not been investigated. Here, we studied Calpain function in two models of myogenesis: in vitro analysis of chick myogenic cultures and in vivo analysis of Drosophila melanogaster muscle development. First we showed that Calpain A is important for fly muscle function. In addition, Calpain A knockdown reduced lateral body wall muscle length and width, as well as the number of nuclei in dorsal oblique muscles, consistent with fewer cells fusing to form fibers. Treatment of chick cultures with a selective Calpain inhibitor led to the formation of thinner myotubes containing a reduced number of nuclei, consistent with decreased myoblast fusion. Dynamic changes in IκBα labeling and transfection with a dominant‐negative IκBα suggest a role for the NFκB pathway during chick myogenesis and a possible role of Calpains in attenuating NFκB signals that restrict myoblast fusion. Our data suggest that different model organisms may be used to study the role of Calpains in regular myogenesis and Calpain‐related muscular degenerative disorders. genesis 53:417–430, 2015. © 2015 Wiley Periodicals, Inc.